2007
DOI: 10.1007/s10488-007-0149-4
|View full text |Cite
|
Sign up to set email alerts
|

Family Advocacy, Support and Education in Children’s Mental Health: Results of a National Survey

Abstract: In conjunction with the national survey of mental health service organizations (Schoenwald et al. this issue), a separate but complementary national survey was conducted of family advocacy, support and education organizations (FASEOs). Directors of FASEOs within the same localities as the mental health agencies responded to a survey and provided information in four areas: (1) structure and funding; (2) factors influencing advocacy decisions about children's mental health; (3) types of services provided by FASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 10 publications
2
34
0
Order By: Relevance
“…as identified in the importance cluster report (see appendix), average ratings (4.72) make this cluster the most important of the six clusters. The relative importance of this cluster and the individual statements contained within this cluster are consistent with the widespread value generally placed on system of care principles, which are reflected in these statements (hoagwood et al, 2007;Munson, hussey, stormann, & King, 2009). These statements also share a common goal of supporting family empowerment, which has been linked to higher retention and effective service use as well as parent knowledge and self-efficacy, all of which are important priorities for service providers (hoagwood, 2005).…”
Section: Cluster Conceptssupporting
confidence: 70%
See 1 more Smart Citation
“…as identified in the importance cluster report (see appendix), average ratings (4.72) make this cluster the most important of the six clusters. The relative importance of this cluster and the individual statements contained within this cluster are consistent with the widespread value generally placed on system of care principles, which are reflected in these statements (hoagwood et al, 2007;Munson, hussey, stormann, & King, 2009). These statements also share a common goal of supporting family empowerment, which has been linked to higher retention and effective service use as well as parent knowledge and self-efficacy, all of which are important priorities for service providers (hoagwood, 2005).…”
Section: Cluster Conceptssupporting
confidence: 70%
“…statements in this cluster (rating importance 2.55) represent ways in which the services could have been, and were, developed and delivered within the Kansas system (Psts as professional vs. volunteer positions, within vs. affiliated with CMhCs, etc.). in addition, these statements present the variation in ways that professional parent services have developed and are provided in other states as well as in other organizations outside the CMhC system in Kansas (davis et al, 2010;hoagwood et al, 2007). because respondents in this study are associated with Pst services provided through the CMhC system, they may or may not have been previously familiar with these other potential options for service provision.…”
Section: Figure 1 Importance Rating Map Showing the Average Cluster mentioning
confidence: 99%
“…In 1997, Heflinger et al noted that ''The parent advocacy movement in children's mental health services has learned from its counterpart in special education, but achievements still lag behind those in general education'' (p. 185). Despite the increasing use of formal peer supports or advocates to increase family involvement in children's mental health services, the literature contains few accounts of specific models and related processes (Hoagwood 2005;Hoagwood et al 2008). Similar to other recent reviews (cf.…”
Section: Peer Providers As Parent Supports In Children's Mental Healthmentioning
confidence: 90%
“…Similar to other recent reviews (cf. Hoagwood et al;Walter and Petr 2006) we found limited peer-reviewed mental health literature describing parent advocate services or how such services are linked to individualized care or improved child and family outcomes. In fact, a 10-year gap appears to exist between the first such studies and what has been published most recently.…”
Section: Peer Providers As Parent Supports In Children's Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation